Estrés laboral, hábitos alimentarios, actividad física y estado nutricional de agentes policiales de la comisaría 09 de octubre, Iquitos.2021 - Tenorio Hurtado, Darian Nadine (2022)
The present research study aimed to determine the correlation of the level of work stress, eating habits, level of physical activity with the nutritional status of police officers of the Commissioner 09 October, Iquitos, 2021. The study was of quantitative approach, nonexperimental type, descriptive design and cross-sectional. The sample consisted of 66 police officers. The data collection used a questionnaire on work stress, eating habits and physical activity and anthropometric measuring instruments; we found: low work stress level with 87.9% and intermediate with 12.1%; adequate eating habits with 7,6% and regular with 92.4%; low physical activity with 57.6%, moderate with 34.8% and high with 7.6%; nutritional status according to normal BMI with 18.2%, overweight with 36.4%, obesity type I with 30.3% and obesity type II with 15.2%; nutritional status according to percentage of normal fat with 27,3%, high with 28.8% and very high with 43.9%; nutritional status according to abdominal perimeter at low risk with 34.8%, high risk with 25.8% and very high risk with 39,4%; there is a highly significant statistical relationship between eating habits and BMI with body fat percentage and abdominal perimeter, also in the variable physical activity with BMI, body fat percentage and abdominal perimeter. Finally, there is a significant statistical relationship between eating habits and physical activity levels and the nutritional status of police officers at the 9th October police station in the city of Iquitos.